2016
DOI: 10.1051/matecconf/20178702002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarettes Smoking on Pulmonary Function among University Students

Abstract: Abstract. Pulmonary function testing is a physiological test that measures how an individual inhales or exhales volumes of air as a function of time. Smoking is greatly associated with reduction of pulmonary function. This research is aimed to estimate the values of peak expiratory flow (PEF), forced expiratory volume in first second (FEV1), forced vital capacity (FVC) and ratio between FEV1/FVC among smoking and non-smoking students in Universiti Tun Hussein Onn Malaysia. Smoking is often related to obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The results of the current study regarding the correlation between the smoking duration and the PF came in accordance with the results reported by Hariri and Wan Mansor who found significant correlation between the number of cigarettes and smoking duration with the reduction in the smoker's FVC and FEV1,[ 22 ] this correlation follows a dose-dependent relationship[ 20 ] and the cigarettes smoking dose was the significant predictor of the level of decrease in the FVC and FEV1. [ 22 ] Additionally; previous studies reported reduced FVC, FEV1, FEV1/FVC and Forced Expiratory Flow rate among adult smokers[ 45 46 ] that indicate affection of the small airways and airways obstruction,[ 47 ] with the severity of affection directly depends on the intensity of cigarette smoking. [ 48 ]…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study regarding the correlation between the smoking duration and the PF came in accordance with the results reported by Hariri and Wan Mansor who found significant correlation between the number of cigarettes and smoking duration with the reduction in the smoker's FVC and FEV1,[ 22 ] this correlation follows a dose-dependent relationship[ 20 ] and the cigarettes smoking dose was the significant predictor of the level of decrease in the FVC and FEV1. [ 22 ] Additionally; previous studies reported reduced FVC, FEV1, FEV1/FVC and Forced Expiratory Flow rate among adult smokers[ 45 46 ] that indicate affection of the small airways and airways obstruction,[ 47 ] with the severity of affection directly depends on the intensity of cigarette smoking. [ 48 ]…”
Section: Discussionsupporting
confidence: 91%
“…[ 21 ] Although smoking control is a pivot health concern, unfortunately; There is limited understanding of the impact of cigarette smoking on pulmonary health as well as functional performance (FP) among the university students, this is in part due to the limited number of studies conducted to evaluate the PF and FP among smokers youth and university smoker students. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study are similar to a study done by Azian Hariri et al, on university students in Malaysia, which also showed a decrease in FVC and FEV1 in smokers. 7 A similar study done by Yang SC showed an irreversible decrease in FEV1 and FVC. 8 However a similar study done in Pakistani adults by Shireen Jawed et al, showed decline in FVC, FEV1 and the FEV1/FVC ratio and also a dose response relation between history of smoking and duration of smoking.…”
Section: Discussionmentioning
confidence: 62%
“…Although the men in our study were relatively young, nearly half were already living with moderately severe COPD. Our age‐related findings may be partly explained by the men's smoking histories (Hariri & Mansor, 2017). Most of the men in this study were former smokers who had consumed a mean of 38.78 ( SD = 23.32) pack year.…”
Section: Discussionmentioning
confidence: 91%